Is ‘elderspeak’ always inappropriate? An empirical investigation of the use of elderspeak in dementia care in the acute hospital context - Bridgstock, Lauren (2025)
The acute hospital environment is known to be difficult for people living with dementia (PLWD), and healthcare staff often view communication with this group as challenging (Griffiths et al., 2014). Elderspeak has been defined as a form of communication used towards older people, particularly PLWD. It involves features such as high pitch/tone of voice, simplified sentences/grammar, terms of endearment and excessive praise. It is often assumed to be patronising or infantilising (Ryan et al., 1995; Williams et al., 2017; Shaw and Gordon, 2021). However, prior research has neglected to examine interactional functions of elderspeak style talk in real life interactions with PLWD. This thesis uses conversation analysis to examine functions of elderspeak style talk within a collection of video data recorded on UK hospital wards during two NIHR funded research projects (VOICE and VOICE2). The data comprise routine healthcare interactions between PLWD and healthcare professionals. Findings suggest that aspects of elderspeak are recurrently used in very specific contexts and appear to fulfil important interactional functions in these contexts. For example, terms of endearment serve mitigating functions and can help orient to conversational closings. Praise works as a supportive action to aid orientation to tasks and activities and has implications for the preservation of agency and face (Goffman, 1955). Finally, prosody (pitch, tone, duration and amplitude of talk) has been shown to systematically draw attention to greetings, convey key messages in talk and add additional layers of meaning to turns. These findings suggest that judgements on elderspeak need to be sensitive to context, as well as contributing to the empirical literature on interactions with PLWD and healthcare communication more widely.